Scrap happens: A case of industrial end-users, maintenance and component remanufacturing outcome. (10th March 2019) - Diener, Derek L.; Kushnir, Duncan; Tillman, Anne-Marie
Abstract: Extended product life and reuse are cornerstones of the circular economy vision. Remanufacturing is one strategy that could be used to facilitate more reuse. Research on remanufacturing often addresses the use phase of a product from the perspective of the remanufacturer, not of the end-user of the product. Results are often described in terms of barriers and drivers, with end-user awareness of and trust in remanufactured products being common themes. It can be argued that such explanations are not sufficient for understanding why remanufacturing doesn't happen because they marginalize events during the use phase and the effects of end-user action. The study described here focuses on the use phase and the end-users' role in product remanufacturing outcome. The study is based on the case of one type of mechanical component, prolific in industry and society at large, and ten of its end-users in heavy industry. The component is already remanufacturable and a functioning remanufacturing system for it is already in place, yet the bulk of used component s are scrapped by end-users instead of being sent for remanufacturing. Interviews were conducted with maintenance personnel at ten paper, steel and cement factories. These personnel were asked how they determine when a component is obsolete and how they make decisions about whether to send them for remanufacturing. Responses were analyzed with the help of theories from maintenance management and decision-making. The analysis is presented as a conceptual model of the 'End-user system' of the component, in which complicating factors such as machine irregularities and tough work environments are mitigated by maintenance personnel with component replacement and remanufacturing protocols and where rigidities related to system-level risks and costs make it difficult for personnel to change. This study reveals the systemic nature of component remanufacturing outcomes, and specifically, how maintenance activities of both components and the machines around them influence such outcomes. Moreover, it highlights that while certain replacement protocols lend themselves to remanufacturing, convincing end-users to choose remanufactured products may be more difficult than just making them aware and confident in the remanufacturing offering. Highlights: Investigates why remanufacturable machine components in heavy industry are routinely scrapped. Maintenance personnel are interviewed about component obsolescence and remanufacturing. Presents a model of the end-user system from interviews, maintenance and decision-making theories. Indicates that increasing end-user choice of remanufacturing requires a systemic approach.